Nuevas nociones sobre el género ficus en colombia (1943)
Ficus andicola / Ficus atrox / Ficus Ciroana / Ficus Danielis / Ficus dendrocida / Ficus Dugandii / Ficus Eliadis / Ficus expansa / Ficus fresnoensis / Ficus frígida / Ficus glaucescens / Ficus Hartwegii / Ficus Hemsleyana / Ficus involuta / Ficus Lehmannii / Ficus macrosyce / Ficus Mathewsii / Ficus mollicula / Ficus Mutisii / Ficus Niceforoi / Ficus ocoana / Ficus ovalifolia / Ficus palmicida  / Ficus panamensis / Ficus polycarpos / Ficus Trianae  / Ficus zarzalensis.